Implementing Fiqh Education to Improve Students' Awareness of Worship at Tri Bhakti At-Taqwa Madrasah Tsanawiyah - Fatimatuzzahroh, Diah; Asy’ari, Hasyim; Hayati, Rina Mida (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to analyze the implementation of Fiqh learning in enhancing students’ awareness of worship at a Madrasah Tsanawiyah (Islamic junior secondary school). Fiqh learning plays a strategic role in shaping students’ religious character, particularly in understanding and practicing worship in accordance with Islamic teachings. This research employed a qualitative approach, with data collected through observations, interviews, and documentation studies. The implementation of Fiqh learning was examined through three indicators: lesson planning, instructional implementation, and learning evaluation. The research participants consisted of the school principal, Fiqh teachers, and seventh-grade students. The findings reveal that effective implementation of Fiqh learning involves the use of various instructional methods, including lectures, discussions, case studies, and direct practice of worship activities. Supporting factors that contribute to the success of the learning process include a conducive learning environment and effective communication skills. The study concludes that interactive and experience-based Fiqh learning can significantly improve students’ awareness of worship. Therefore, innovative learning strategies, improved teaching quality, and strong collaboration among schools, families, and communities are essential for creating a supportive environment that fosters the development of students’ religious character.